Analysis PM2.5 Removal Efficiency and Electrical Energy Consumption in The Use of Air Purifier and Air Conditioner in a Room - Melani Febriwati; Arie Dipareza Syafe’i (Jurnal Serambi Engineering, 2024)
Indoor air quality is important for an individual's quality of life because humans often spend 90% of their time indoors. Indoor air quality impacts human comfort, health, and performance. This research aims to identify the effect of variations in AC temperature control systems and air purifier fan speed on PM2.5 concentrations, as well as indoor thermal comfort and recommendations for AC and AP settings to remove PM2.5 with high efficiency and lower electrical energy with statistical tests. The highest percentage of PM2.5 removal when the AC was set to a temperature of 22°C with the AP turned on automatically, namely 89.7% in removing PM2.5. The lowest percentage of removal of PM2.5 concentrations when the AC temperature was set to be turned on at 25°C with the AP set turned off, namely 40.57%. The first recommendation is to set the AC to be turned on at 25°C and the AP to be turned on automatically, which has a percentage of 84.72% with a monthly price of 17,400 IDR. The second condition that can be recommended is setting the AP to be turned on automatically, but the AC set turned off, which has a percentage of 88.34% for 1,800 IDR.